FREE NIPPLE GRAFT: CURRENT INDICATIONS AND APPLICATIONS OF A CENTENARY BREAST SURGERY TECHNIQUE – A LITERATURE REVIEW - Leon, Rafael Araujo Ponce de (Mastology, 2026)
Objective: This literature review seeks to provide an updated synthesis of knowledge about the free nipple graft (FNG) technique and its outcomes relating to aesthetic satisfaction, functionality, and safety profile, as well as to analyze its incorporation and applicability in several intervention areas involved in mastology such as mammaplasty, transgender, and oncoplastic surgery. Methods: A structured electronic literature search was conducted, using the PubMed and LILACS databases. The search strategy consisted of the keywords, MeSH terms, and free text words for the FNG and its application in mammaplasty, transgender, and oncoplastic surgery. Results: A total of 397 articles were found and after inclusion and exclusion criteria, 15 were selected. Their outcomes have shown, despite the lack of standardized scores to postulate better scientific evidence on its use and indications, that the technique, analyzed in over 1290 patients, achieved high-safety rates and reproducibility. Aesthetic and patient satisfaction were positives and recommended by the authors in different studies discussed in this study. Despite these considerations regarding methodological and article limitations, it is important to emphasize a broad applicability of the FNG technique and its limited dissemination and use in breast surgery. Notwithstanding inconveniences related to the FNG technique, such as total loss of nipple sensibility, areolar depigmentation, and flattening of the papilla over time, it is also necessary to reinforce the low rate of loss of graft. Moreover, in cases of oncological surgeries, in which maintaining NAC would not be possible after mastectomy in ptotic or bulky breasts, FNG may be used for the maintenance of the nipple-areolar complex or correction of malposition of it after conservative or radical mastectomies. Conclusion: The literature data analysis provides a broad view of possibilities in breast surgery using the FNG technique and its safety profile. This study represents a potential impact on both experienced and learner surgeons when providing the most complete and updated information about a technique with a large spectrum of intervention in either mammaplasty, oncological, or transgender surgery. Still, we reinforce the need for adequate interventional trials and standardized aesthetic functional scores in order to define with a better level of evidence the usefulness of FNG.